2022
DOI: 10.3390/app12136605
|View full text |Cite
|
Sign up to set email alerts
|

Research on Adhesive Coefficient of Rubber Wheel Crawler on Wet Tilted Photovoltaic Panel

Abstract: The demand for renewable energy sources is growing fast because of the negative impact of the utilization of fossil energy, nuclear energy, and hydroelectricity. One of the renewable energy sources, known as solar energy, which uses the photovoltaic panel (PV) to generate electricity from the sun, is a promising alternative that has great potential to deal with the power crisis. However, the power productivity and efficiency conversion are affected significantly by dust accumulation on PVs. Many researchers in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…The parameter table is presented below (Table 3). In comparison with references [14][15][16][17][18][19][20][21][22], the self-propelled photovoltaic cleaning robot developed in this study showed the following advantages:…”
Section: Kinematics Analysismentioning
confidence: 84%
See 1 more Smart Citation
“…The parameter table is presented below (Table 3). In comparison with references [14][15][16][17][18][19][20][21][22], the self-propelled photovoltaic cleaning robot developed in this study showed the following advantages:…”
Section: Kinematics Analysismentioning
confidence: 84%
“…With the cross-arm structure of the photovoltaic panel cleaning robot as the research object, Hou et al [19] adopted topology optimization for the lightweight design of the cross-arm structure based on the power correlation analysis, which increased the safety and practicality of the cross arm. Nguyen et al [20] investigated the rubber tracked photovoltaic panel cleaning robot while exploring the problem of this type of robot slipping on wet photovoltaic panel surfaces in depth. They built a theoretical model and analyzed it.…”
Section: Structural Designmentioning
confidence: 99%
“…Crawler on Wet Tilted Photovoltaic Panel [13] The article mentions the relationship between the properties of PV panels and SPCR, specifically the sliding phenomenon when SPCR moves on an inclined surface. The article also provides methods to solve the problem.…”
Section: Research On Adhesive Coefficient Of Rubber Wheelmentioning
confidence: 99%
“…Slip resistance has been recognized as the key feature of the belt-based track, aiming to enhance the anti-slippage capability of this specific PV cleaning robot. Although numerous studies ( [33][34][35][36] and references therein) have investigated the effects of rubber soling materials on floor surfaces, there has been limited research, except for our earlier study [37,38], regarding suitable material coatings for the belt-based track that can provide sufficient grip for the PV cleaning robot during the removal of dust from wet PV panels. It was observed that shore hardness and surface roughness significantly impact the slip resistance of rubber soles in both dry and wet flooring conditions [33].…”
Section: Introductionmentioning
confidence: 99%